Academic bullying among faculty personnel in Estonia and Finland. Issue 3 (4th May 2019) - Meriläinen, Matti; Käyhkö, Katinka; Kõiv, Kristi; Sinkkonen, Hanna-Maija
ABSTRACT: This comparative study focuses on the prevalence, nature, and manifestations of experienced bullying among faculty personnel, that is, both academic and management staff of universities in Estonia and Finland. A total of 1, 191 respondents from Estonia (n = 864) and Finland (n = 327) responded to identical questionnaires. The results show that 27 per cent of respondents in Estonia and 18 per cent in Finland had experienced bullying within six months prior to the study. In Estonia bullying is most commonly straightforward and may include insulting an individual in the presence of colleagues, while in Finland people typically get indirectly slandered behind their back. In Estonia, work-related threats of blame, violence, humiliation and ridicule are typical, whereas it is more ordinary to make negative work-related remarks in Finland. The dissimilar factor models and the categories based on open-ended answers also confirm the presupposition of academic bullying as a culture-related phenomenon.